A case study of one Midwestern elementary professional development school’s experiences in hiring student teachers upon graduation - Morgan, Nicholas (Kansas State University, 2019)
Although there is a vast amount of professional literature on the hiring process in the K-12 educational setting, the research on how hiring teams identify effective student teachers to be employed at their schools after graduation is limited. This area is significant to educational leaders across the United States because of alarming recent teacher shortage and retention data. This study addressed a gap in the literature by providing information on the hiring process implemented by one rural Midwestern elementary professional development school (PDS) pertaining to student teachers who completed student teaching at that site. This qualitative single case study used the Behavior-Based Interviewing (BBI) model and teacher characteristics and abilities found on one state department’s educator evaluation protocol as the method to examine this PDS’ experiences in its hiring process of graduated student teachers. Five participants were interviewed for this case study including the principal, an assistant principal, a non-classroom teacher, and two classroom teachers employed at this school. This study identified the following themes contributing to an effective hiring process. During the student teaching experience, hiring team members considered the performance and general personality characteristics of the student teacher along with how the potential hire would fit within expectations for the present school culture. School leaders implemented distributed leadership principles by working collaboratively with the hiring team in making employment decisions. Finally, certain components of the BBI model were present in the hiring process.
Keywords: Student teacher; Hiring process; Elementary school; Professional development school; Midwest USA; Behavior Based Interviewing